Feeling-of-knowing experiences breed curiosity. Issue 2 (7th February 2021) - Brooks, Gregory; Yang, Haopei; Köhler, Stefan
ABSTRACT: A central tenet in theoretical work on metacognition is that retrieval experiences during memory search can exert control over behaviour. States of curiosity, which reflect motivational tendencies to seek out information, may play a critical role in this control function. We conducted two experiments to address this idea, focusing on links between feeling-of knowing (FOK) experiences, memory-search duration, and subsequent information-seeking behaviour. We administered an episodic FOK paradigm that probed memory for previously studied face-name pairs, and subsequently provided an opportunity to select limited pairs for restudy. This set-up allowed us to test whether current search duration and subsequent restudy choices are biased towards items with high FOK ratings. Results revealed a positive relationship between FOK ratings and the response times of these judgements. We observed a similar positive relationship between FOK ratings and subsequent item selection for restudy. Moreover, experimental manipulations of FOK ratings based on familiarity of the face cues also had parallel effects. Our findings suggest that metacognitive experiences during unsuccessful retrieval from episodic memory can induce states of curiosity that shape behaviour beyond the immediate retrieval context. Curiosity may act as a bond to ensure that memory gaps identified through unsuccessful retrieval adaptively guide future learning.